Application of a Difference Electron Nanoscope (DEN) – a computer hard‐ and software to display 3D electron densities and magnetical structures based on spectroscopic and diffractometric data. Issue 1 (29th October 2013) - Lottermoser, W.; Steiner, K.; Scharfetter, G.; Weber, S.‐U.; Grodzicki, M.; Kirfel, A.; Amthauer, G.
<x xml:space="preserve">Abstract</x> M1 position of synthetic fayalite at 0.5, 0.5, 0.5 with a blue wire frame model representing the electric field gradient, surrounding difference electron densities (light brown) from synchrotron diffraction data and direction of the internal magnetic field H(0) at 50K (red arrow) from Mössbauer spectroscopy <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>